2022
DOI: 10.1038/s41433-021-01912-4
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of early diabetic retinopathy staging in asymptomatic patients between autonomous AI-based screening and human-graded ultra-widefield colour fundus images

Abstract: Introduction Comparison of diabetic retinopathy (DR) severity between autonomous Artificial Intelligence (AI)-based outputs from an FDA-approved screening system and human retina specialists’ gradings from ultra-widefield (UWF) colour images. Methods Asymptomatic diabetics without a previous diagnosis of DR were included in this prospective observational pilot study. Patients were imaged with autonomous AI (IDx-DR, Digital Diagnostics). For each eye, two 4… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 38 publications
(41 reference statements)
1
8
0
Order By: Relevance
“…There have been numerous studies looking into the performance of AI DR software against human graders of different specialty and training levels, and AI DR algorithms show significant performance differences [ 11 , 12 ]. Recently Sedova and colleagues compared the performance of IDx-DR with seven-field ETDRS protocol fundus images and ultra-wide-field images graded by two retinal specialists [ 13 ]. They found IDx-DR results to have a 66.6% and 66.7% agreement with seven-field and ultra-wide-field examinations, respectively, with respective kappa scores of 0.40 and 0.38 [ 13 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…There have been numerous studies looking into the performance of AI DR software against human graders of different specialty and training levels, and AI DR algorithms show significant performance differences [ 11 , 12 ]. Recently Sedova and colleagues compared the performance of IDx-DR with seven-field ETDRS protocol fundus images and ultra-wide-field images graded by two retinal specialists [ 13 ]. They found IDx-DR results to have a 66.6% and 66.7% agreement with seven-field and ultra-wide-field examinations, respectively, with respective kappa scores of 0.40 and 0.38 [ 13 ].…”
Section: Discussionmentioning
confidence: 99%
“…Recently Sedova and colleagues compared the performance of IDx-DR with seven-field ETDRS protocol fundus images and ultra-wide-field images graded by two retinal specialists [ 13 ]. They found IDx-DR results to have a 66.6% and 66.7% agreement with seven-field and ultra-wide-field examinations, respectively, with respective kappa scores of 0.40 and 0.38 [ 13 ]. Of note, in the current study, both AI and human graders had access to the same information (only standard color macula- and disc-centered fundus images), whereas Sedova et al compared IDx-DR output to graders using more comprehensive imaging studies.…”
Section: Discussionmentioning
confidence: 99%
“…[20][21][22] Studies done at other institutions produced similar results, demonstrating the real-world utility of these systems. 84,[88][89][90] For example, Mehra et al reported that the integration of IDx-DR in a primary care clinic DR screening program resulted in 100% sensitivity and 89% specificity for mtmDR. 88 Kim et al combined EyeArt with smartphone-based retinal photography, achieving a lower sensitivity but higher specificity than trained expert graders.…”
Section: Artificial Intelligence-based Image Analysismentioning
confidence: 99%
“…Comparative studies between non-mydriatic or mydriatic UWF images and ETDRS seven-field standard images were investigated [ 32 , 33 , 34 , 35 , 36 , 37 ]. Automated DR diagnosis in fundus photography, one of the software with artificial intelligent was recently approved by FDA, adopts two-fields photographs [ 38 ], and such cost-effective screening of this disease is another hot topic.…”
Section: Evolutions Of Contemporary Modalities In Imaging Of Drmentioning
confidence: 99%
“…This system diagnosis with two conventional 45-degree photographs of macular-centered and disc-centered and was reported to offer sufficient quality of detecting referable DR compared to human grading [ 16 ]. Many studies also reported high rate of sensitivity and specificity of autonomous-AI diagnosis system in diagnosing any stage of DR [ 38 , 90 , 91 , 92 , 93 , 94 , 95 ]. Diagnostic sensitivity of the algorithm (2iRetinex) for DR to sight threatening vision was examined, and the sensitivity is nearly identical to diagnosis by physician [ 92 ].…”
Section: Recent Topics In Imaging In Drmentioning
confidence: 99%